Exploring Intersection of Migration and Urban Space in Jakarta - Kilim Park (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2017)
Stories of migration tend to mark monumental moments in people's lives. In Indonesia, the experiences of labour migrants, in particular, female overseas domestic workers (usually referred to as TKW: Tenega Kerja Wanita), continue to make the news and has made its way into the Indonesian popular culture as well. In this conceptual paper, I offer a brief observation on the discussion of labour migration in Indonesia, and propose new ways to explore migration and urban space. In particular, with a focus on intersectionality of the two with respect to migrant women returnee's experience, I propose an approach that considers the details in their everyday lives and reflections upon them intertwined with formal and informal aspects of urban citizenship. Finally, by using Jakarta as a case study of urban space where migrant returnees live in, and influence and change, I suggest a research direction that centralizes migrant women as a storyteller and keyplayer in our understanding of urban, social, and cultural change in Indonesia and broadly, Southeast Asia.